Confessions to Mr Big: A new rule of evidence?. (January 2016) - Murphy, Brendon; Anderson, John
In Queen v Hart, the Supreme Court of Canada recognised what was described as a 'new rule of evidence' concerning confessions obtained during 'Mr Big' operations. This undercover policing technique is known to be a time-intensive but effective strategy in the investigation of cases in which suspects are highly secretive. In Hart, the Canadian Supreme Court recognised the value of this form of investigation, but emphasised that such strategies require careful scrutiny by the judiciary because of the potential for unethical policing and the unreliability of confessions in cases where this evidence is obtained in association with 'entrapment' strategies. This article examines the 'novel' jurisprudence in Hart, and considers its utility in the context of other common law countries, particularly Australia where uniform evidence legislation applies in the majority of jurisdictions. Ultimately it is contended that the 'new rule of evidence' in Hart is effectively a specific adaptation of well-known rules of evidence in the extant common law and legislation of Australia, England and New Zealand and, therefore, of limited utility outside Canada.